3D analytical method for the external dynamics of ship collisions and investigation of the coefficient of restitution - LIU Junfeng; HU Zhiqiang (Zhongguo Jianchuan Yanjiu, 2017)
The analytical method for predicting the dynamic responses of a ship in a collision scenario features speed and accuracy,and the external dynamics constitute an important part. A 3D simplified analytical method is implemented by MATLAB and used to calculate the energy dissipation of ship-ship collisions. The results obtained by the proposed method are then compared with those of a 2D simplified analytical method. The total dissipated energy can be obtained through the proposed analytical method, and the influence of the collision heights,angles and locations on the dissipated energy is discussed on that basis. Furthermore,the effects of restitution on the conservative coefficients and the effects of conservative coefficients on energy dissipation are discussed. It is concluded that the proposed 3D analysis yields a lesser energy dissipation than that of the 2D analysis,and the collision height has a significant influence on the dissipated energy. In using the proposed simplified method,it is not safe to simplify the conservative coefficient as zero when the collision angle is greater than 90 degrees. In the future research, to get more accurate energy dissipation, it is a good way to adopt the 3D simplified analytical method instead of the 2D method.